In-Group Bias in Preferences for Redistribution: A Survey Experiment in Italy - Riccardo Bruni; Alessandro Gioffré; Maria Marino (Center for Economic Studies and ifo Institute (CESifo), 2023)
Using a new survey and experimental data, we investigate how information on inequality and immigration affects preferences for redistribution in Italy. Our randomized treatments show that preferences for redistribution are generally inelastic to information. However, we find that provision of information on poverty statistics related to the native-immigrant composition of poverty reduces economic in-group bias by affecting exclusionary redistributive preferences. Respondents are less likely to support policies that exclude immigrants from access to the welfare state once they learn that immigrants are less represented among the poor and natives are not as poor as believed. We also find evidence of cultural in-group bias by investigating heterogeneous treatment effects on policy preferences across socio-demographic groups.
Keywords: D91; D72; H23; H24; C83; 330; inequality; immigration redistribution; perception; survey experiment